Answer:MON=99
Step-by-step explanation:
8x-13+7x-17=180
15x=210
x=14
Step-by-step explanation:
We are asked to simply (2√5 + 3√2)². Using formula: (a + b)² = a² + b² + 2ab. Let's say 2√5 = a, 3√2 = b. So,
→ (a + b)² = a² + b² + 2ab
→ (2√5 + 3√2)² = (2√5)² + (3√2)² + 2(2√5)(3√2)
We are aware about the fact that root means 1/2 and square of root means 2/2 that is 1. Using this we get:
→ (2√5 + 3√2)² = 4(5) + 9(2) + 2(2√5)(3√2)
Solve the brackets, to do so first put the like terms in one box.
→ (2√5 + 3√2)² = 4(5) + 9(2) + 2(2*3)(√5)(√2)
Solve the rest calculations.
→ (2√5 + 3√2)² = 20 + 18 + 2(6)(√10)
→ (2√5 + 3√2)² = 38 + 12√10
Option (a) (38 + 12√10) is the correct option.
Answer:
D) 3.28
Step-by-step explanation:
820/x=100/2.5
(820/x)*x=(100/2.5)*x - we multiply both sides of the equation by x
820=40*x - we divide both sides of the equation by (40) to get x
820/40=x
20.5=x
x=20.5
now we have:
2.5% of 820=20.5
I think its (6.5+3.25)÷0.2=48.75
dont quote me on that, I tried and I'm not the best at math lol.
Answer:140W
Step-by-step explanation: